State of the art survey on security issue in cloud computing architectures, approaches and methods - RAZZAQUE, MOHAMMAD (My University, 2015)
The development of cloud computing has revolutioniz ed in how the computing and storage are utilized remotely. It has grown from being hopeful business concept to one of the fast growing segments of the IT manufacturing. It has become attractive to business es and organizations. Although of all the benefits of the cloud, enterprise customers are still unwilling to position their business in the cloud. Security and privacy are the main issues which decrease the growth of cl oud computing and preservation of data continue to plague the market. In this paper, we present the vu lnerabilities and attacks; identify relevant soluti on directives to strengthen security in the cloud envi ronment. The main goal of this paper is to offer a better understanding of the security challenges of cloud c omputing and identify architecture, approaches and methods that have been proposed.
Keywords: cloud computing